REDEFINING WORKPLACE SEXUAL HARASSMENT IN GHANA - Addadzi-Koom, Maame Efua Addadzi-Koom (UCC Law Journal, 2025)
Sexual harassment became topical in Ghana and Nigeria when BBC Africa Eye released the Sex for Grades documentary in the last quarter of 2019. The documentary implicated some lecturers in public universities. Nigeria’s Parliament promptly passed an anti-sexual harassment law. However, Ghana’s Parliament deliberated on the subject and has yet to pass an anti-sexual harassment law. The current legal regime on sexual harassment in the workplace in Ghana is limited. Accordingly, I advocate for a comprehensive law prohibiting all forms of sexual harassment in the workplace. I use doctrinal analysis to examine the existing laws on sexual harassment in Ghana and recommend redefining them expansively drawing comparative insights from Nigeria and South Africa.